An active seat suspension design for vibration control of heavy-duty vehicles - Ning, Donghong; Sun, Shuaishuai; Zhang, Jiawei; Du, Haiping; Li, Weihua; Wang, Xu (Journal of low frequency noise, vibration, and active control, 2016)
This paper presents the design, fabrication and testing of an innovative active seat suspension system for heavy-duty vehicles. Rather than using conventional linear actuators, such as hydraulic cylinders or linear motors, which need to be well maintained and are always expensive when high force outputs are required, the proposed seat suspension system directly applies a rotary motor in order to provide the required active actuation, without changing the basic structure of the existing off-the-shelf seat suspension. A gear reducer is also applied to amplify the output torque of the motor so that a high output torque can be achieved using a low rated power motor. A static output feedback H ∞ controller with friction compensation is designed to actively reduce seat vibration. Experiments are carried out to test the fabricated suspension prototype. The experimental results show that this type of seat suspension can achieve greater ride comfort in the frequency range of 2–6 Hz than a passive seat suspension. The newly designed active seat suspension is much more cost effective and can be suitable for heavy-duty vehicles.